The association between lutein and zeaxanthin intake and multi-level biological aging - Tao, Meiyi; Zhang, Lin; Jiang, Caidi; Xiang, Jia; Chen, Shipeng; Tan, Songwen; Sun, Shengli (Frontiers in Nutrition, 2025)
ObjectiveThis study investigates the potential association between lutein and zeaxanthin (LZ) intake, particularly lutein, and biological aging. The study aims to explore how LZ intake affects the biological aging progression, particularly in organs like the liver, kidneys, and cardiovascular system, and explore the potential mechanism of lutein as the main carotenoid mediating this effect.MethodsWe analyzed biological aging using biological age calculations based on data from the NHANES 2007–2015 database. Various adjusted models were used to assess the relationship between LZ intake and aging phenotypes. Transcriptome analysis was conducted to explore the potential mechanisms underlying the anti-aging effects of lutein.ResultsA higher intake of LZ was associated with a slower biological aging rate (P < 0.01), observed in major organs such as the liver and kidneys, as well as the cardiovascular system. LZ intake showed a significant negative correlation with biological aging acceleration (P < 0.05). Enrichment analysis suggested that lutein's anti-aging effects might be mediated through telomere regulation and modulation of aging-related metabolic pathways. Additionally, lutein intake appeared to reduce pro-inflammatory Th1 cell abundance, further suggesting a potential anti-aging effect by suppressing inflammation. Sustained lutein intake also led to a decrease in the expression of aging phenotype-related molecules. However, in the evaluation of linear relationships, excessive lutein intake beyond a certain threshold may not yield additional benefits.ConclusionCombined LZ intake is associated with attenuated multi-level biological aging [OR (95% CI): 0.93 (0.88, 0.93), P = 0.016] and high LZ intake significantly reduce the risk of all-cause death (P < 0.001), with lutein driving systemic effects via telomere regulation and inflammation suppression. These findings highlight lutein's translatable potential for aging interventions and provide insights for dietary strategies in aging health management.